Simple and efficient transcutaneous inductive micro-system device based on ASK modulation at 6.78 MHz ISM band - Alghrairi, Mokhalad Khaleel; Kadhim, Imam; Sulaiman, Nasri; Mohd Sidek, Roslina; Mutashar, Saad (2020)
This paper deals with designing a simple and efficient simultaneous inductive power and data transmission for transcutaneous Micro-system based on ASK modulation at 6,78 MHz industrial, scientific, and medical (ISM) band to avoid the tissue damage. The modified ASK modulator and inductive coupling link driven by efficient Class-E power amplifier with 94,5% efficiency and the coupling link of up to 78,29% of efficiency are introduced to transmit 500 Kbit/s of data with modulation index 12,5%, modulation rate 7,37%. The proposed design is simple, easy to implement and able to power the bio-implantable devices with DC V up to 5 V. The mathematical model is given and the system is designed and validated by professional OrCADPsPice 16,6 environment simulation using a standard AMS 0,35 μm MOS technology. In addition, for real-time simulation, the electronic workbench MULISIM 11 has been used to simulate the class-E power amplifier switching. This design is useful for cochlear implants, retinal implants and implantable micro-system stimulator.